Engine and auxiliary systems - Mohiuddin, A. K. M. (IIUM Press, International Islamic University Malaysia, 2011)
Preface The development of our society is closely related to the improvements in transportation. The Internal Combustion Engines (ICE) occupies a very important position in this development. The purpose of this book “Engine and Its Auxiliary Systems” is to provide updated information on the design, construction and maintenance of the engine and its auxiliary systems. This book does not intend to represent the full body of internal combustion engine technology, but it does provide technical presentations and their reference documents, which can lead the engineer to discussions covering several topics of interest in internal combustion engines and its auxiliary systems. This book is a collection of a series of chapters written by the faculty members of the Mechanical Engineering Department of International Islamic University Malaysia. These chapters are the outcome of different research projects executed by the authors. The chapters were chosen to cover a variety of topics within the area of ICE and its auxiliary systems. These chapters reflect the latest advancement in international combustion engine technology. This should enhance the utility of the book for any person engaged in the pursuit of knowledge of internal combustion engines, particularly the practicing engineers and researchers in the field. The editor would like to extend heartfelt gratitude to all the authors who have contributed chapters for the book. We are also grateful to IIUM press for publishing the book.